Effect of weather and days of the week on number of daily circulation in public libraries - Sato, Sho (2022)
Objective. The study investigated the effect of weather and day of the week on the daily circulation numbers in two public libraries in Japan. Method. Datasets on library circulation were collected from one library in an urban area, and another in a rural area. The data were then divided according to rainy day and other days, holiday and workday, and day of the week, and the presence or absence of significant differences in daily circulation was analyzed. Automatic linear modeling was performed to analyze the effect of weather, day of the week, and holiday on daily circulation. Results. The results revealed that day of the week have a considerable impact on daily circulation for both libraries. However, weather exerted a significant impact in the urban area only. Automatic linear modeling explained the daily circulation based on day of the week and holiday with an accuracy of 71.5% for the rural library, and explained the circulation numbers based on day of the week, holiday, and precipitation amount with an accuracy of 81% for the urban library.